Soft power of the Republic of Korea to the countries of Central Asia - Kosimov Abrorbek; Hikmatulla Kazakbaev (Genius Journals, 2022)
This article touches on the common feature of the soft power of the Republic of Korea in Central Asian countries today, ranging from economic ties to the K-Pop music genre.
Keywords: Soft power; South Korea; Central Asian countries; diplomacy